A Learning Community Model of Graduate Student Professional Development for Teaching Excellence - Shu Barger, Shihmei; Carlson-Drakes, Christopher G.; Brower, Aaron M. (My University, 2007)
A learning community model is presented as a successful approach to teaching-related professional development for research-active future faculty. Four core elements of learning communities are identified: shared discovery and learning, functional relationships, inclusive learning environments, and connections to other learning experiences. These four elements are used throughout learning community programming and activities to foster a sense of shared identity, belonging, ownership, responsibility, and contribution. We describe preliminary indicators of success as we prepare to further test the model.
Keywords: Teaching and Learning